CONFORMITY TO MASCULINE NORMS AND ITS EFFECTS ON MEN’S WELL-BEING (Annual of the Faculty of Philosophy in Skopje, 2020)
Given the body of evidence for the complex links between gender norms andwell-being, examining the effects of masculine norms on men's health is increasinglybecoming a focus of public health interest. This research is an attempt to shed light onthe links between accepting different aspects of the hegemonic masculinity norms withself-esteem and life satisfaction on the one hand and depression, anxiety, stress, emotionalclosure and taking health risks on the other. The sample of participants includedin the research consists of 310 men, ethnic Macedonians from 20 different cities in thecountry, aged between 20 and 30 years.The results of the correlational analysis between the eight included variables, inaddition to clearly confirming the need for analysis of various aspects of masculinity onmen's behaviour, as opposed to using the general score only, suggest that for this agegroup, identification with hegemonic masculinity carries more potential risks than benefits.Thus, while the acceptance of the hegemonic ideal is positively related to self-esteemand life satisfaction in only a small number of aspects, most are associated with areluctance to share emotions, depression, stress, anonymity, and health-threatening behaviours.
Keywords: MASCULINE NORMS; RISK BEHAVIOURS; WELL-BEING